Distribution of brachiopods in the Lower Visean deposits in the Eastern Urals - N. A. Kucheva (Литосфера, 2019)
Subject. This paper is aimed at investigating the distribution of brachiopods across the stratotypes of the Lower Visean regional substages and formations, as well as of the Upper Visean Zhukovsky regional substage, which are presently located in the East Uralian and Magnitogorskian megazones of the Eastern Urals. Materials and methods. Brachiopods were one of the most numerous groups of benthic organisms inhabiting the Early Carboniferous marine basins now located in the eastern Urals. This paper presents information on the distribution of brachiopods across the carbonate and carbonate-terrigenous facies of the Middle (Pokrovskoe, Zhukovo, Smolino, Brod-Kljuchiki) and Southern (Nizhnyaya Gusikha, Verkhnyaya Kardailovka, Kipchak, Ust-Grekhovka and Khudolaz) Urals sections.Results. It is found that Delepinеа lebedevi, D. comoides, Ovatia markovskii and Composita sp. were the domineering species during the Early Visean period. The Ust-Grekhovsky time marked the appearance of migrant species, which resulted not only in a decrease in the proportion of Delepinеа and Ovatia but also significantly changed the entire structure of the local brachiopod communities. The evolutionary transformation of the Ovatia genus at the Ust-Grekhovsky–Zhukovsky time boundary led to the appearance of the Linoprotonia genus and subsequently to the Globosoproductus genus (the first representative of the Gigantoproductini). The Zhukovsky period was characterized by a continuing reorganization of the composition and structure of the communities, featuring a change in the dominant taxa. The Linoprotonia and Globosoproductus genera became widespread. Rare representatives of the Gigantoproductus, Datangia and Semiplanus genera appeared.Conclusions. A direct correlation between the diversity of brachiopod associations and abiotic factors is found. The most diverse associations represented by the taxa of several orders, including Gigantoproductini, inhabited shallow-water environments with carbonate sedimentation. The evolution of brachiopods over the Early Visean and Zhukovsky periods of the Late Visean was characterized by natural succession in the composition of genera and species, with the most significant alteration having occurred in the Ust-Grekhovsky and Zhukovsky periods.